2015
DOI: 10.1021/acs.iecr.5b01165
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Crystallizer-Producing Shape-Engineered Crystals

Abstract: In this work, the two-(2D) and three-dimensional (3D) population balance models of an MSMPR crystallizer have been developed in order to conduct linear stability analysis. A quantitative comparison of the one-dimensional (1D), 2D, and 3D models has been conducted to determine the range of applicability of these models in terms of prediction of the stable behavior of crystallizers. Both dynamic and steady-state models have been solved for two crystals of practical importance: β-Lglutamic acid and hydroquinone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The PBE , for the droplet population is given by eq . Here, ω represents the population density of droplets in the crystallizer, τ represents the droplet age, C ̅ represents the average solute concentration, and C ̅ sol represents the average solvent concentration within the droplets.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The PBE , for the droplet population is given by eq . Here, ω represents the population density of droplets in the crystallizer, τ represents the droplet age, C ̅ represents the average solute concentration, and C ̅ sol represents the average solvent concentration within the droplets.…”
Section: Theorymentioning
confidence: 99%
“…(c) The emulsifiers attached to the droplet interface 58 are assumed to be removed during the filtration, washing, and drying stages and do not end up in the final product agglomerates. The PBE 53,59 for the droplet population is given by eq 1. Here, ω represents the population density of droplets in the crystallizer, τ represents the droplet age, C̅ represents the average solute concentration, and C̅ sol represents the average solvent concentration within the droplets.…”
Section: Theorymentioning
confidence: 99%
“…Crystallization 1 is a widely used separation and purification process, 2,3 which is used to separate the compound of interest from a solvent or a mixture of solvents 4 . As a unit operation, 5 it is used in a multitude of industries including chemical, 6 food processing, 7 petrochemical, and microelectronics 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Mesbah et al designed a closed loop optimal control cooling profile for batch cooling crystallization, using a Luenberger type observer to estimate the state of the system. They found that implementing this closed loop optimal control policy led to a great increase in crystal volume fraction at the end of the batch and the method was also robust to variations between batches Model-based and model-free approaches have also been used to control polymorphic purity during cooling crystallization of small molecules. , There have also been significant advances in modeling the stability of industrial crystallizers, including the case that also considers the evolution of crystals shape, where the principles of optimal control of crystallizers can be used to better predict stability under dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that implementing this closed loop optimal control policy led to a great increase in crystal volume fraction at the end of the batch and the method was also robust to variations between batches Model-based and model-free approaches have also been used to control polymorphic purity during cooling crystallization of small molecules. 17,18 There have also been significant advances in modeling the stability of industrial crystallizers, 19 including the case that also considers the evolution of crystals shape, 20 where the principles of optimal control of crystallizers can be used to better predict stability under dynamic conditions. Although cooling crystallization is the most widely used crystallization strategy, some compounds do not have steep solubility variation with temperature.…”
Section: Introductionmentioning
confidence: 99%